1994
DOI: 10.4319/lo.1994.39.7.1768
|View full text |Cite
|
Sign up to set email alerts
|

Plaster standards to measure water motion

Abstract: Plaster of paris blocks (clod cards) were re‐evaluated as devices to measure water motion in freshwater and marine environments. Clod cards, developed in 1971, have only been used as indicators of relative water motion. We generated standard curves relating the dissolution rates of clod cards to water speed, temperature, and salinity by attaching the cards to a mechanical arm rotating in a tank of water. Free convection experiments were also conducted by suspending clod cards in quiescent solutions held in ice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
87
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 127 publications
(88 citation statements)
references
References 8 publications
0
87
0
Order By: Relevance
“…From these excellent relationships it has often been assumed that it was steady flow speed or current velocity that was measured in the field (e.g., Petticrew and Kalff 1991;Komatsu and Murakami 1994). Moreover, it has been suggested that gypsumdissolution rates be calibrated to flow speeds and reported in velocity units (Thompson and Glenn 1994). In addition, Petticrew and Kalff (1991) suggested that the gypsum-dissolution technique could potentially be used as a turbulence sensor; however, they calibrated dissolution rates exclusively to steady flow speed.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…From these excellent relationships it has often been assumed that it was steady flow speed or current velocity that was measured in the field (e.g., Petticrew and Kalff 1991;Komatsu and Murakami 1994). Moreover, it has been suggested that gypsumdissolution rates be calibrated to flow speeds and reported in velocity units (Thompson and Glenn 1994). In addition, Petticrew and Kalff (1991) suggested that the gypsum-dissolution technique could potentially be used as a turbulence sensor; however, they calibrated dissolution rates exclusively to steady flow speed.…”
Section: Discussionmentioning
confidence: 99%
“…Still-water calibrations to determine this as a ''measure of the degree to which diffusion or dissolution was enhanced by water movement'' (Doty 1971) have given variable results (Muus 1968;Doty 1971) but have been widely used. The variability in the stillwater measurements has been attributed to the small water volume used (Jokiel and Morrissey 1993;Thompson and Glenn 1994), which may have led to less of a concentration gradient in the diffusive boundary layer, and thus a low dissolution rate or saturation of Ca 2ϩ . In addition, the variability has been attributed to placing gypsum devices too close to the bottom of containers (Thompson and Glenn 1994), thereby decreasing the concentration gradient in the diffusive boundary layer and decreasing dissolution rates.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations